2022
DOI: 10.1111/bcp.15215
|View full text |Cite
|
Sign up to set email alerts
|

Pro: Oximes should be used routinely in organophosphate poisoning

Abstract: In poisoning with organophosphorus compounds (OP), patients can only profit from the regeneration of acetylcholinesterase, when the poison load has dropped below a toxic level. Every measure that allows an increase of synaptic acetylcholinesterase (AChE) activity at the earliest is essential for timely termination of the cholinergic crisis. Only drug‐induced reactivation allows fast restoration of the inhibited AChE. Obidoxime and pralidoxime have proved to be able to reactivate inhibited cholinesterase thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Reference or standard oximes are usually specific to individual OP compounds and are not broad-spectrum [ 3 , 4 , 5 , 6 , 7 ]. In addition to the lack of universal access, another problem with reference oximes is their pharmacological properties, which are defined by their rapid dissociation in the body into ionized forms [ 8 , 9 , 10 ]. Hydrophilic oximes with a charged nitrogen atom hardly pass through the blood–brain barrier (BBB) to central synapses.…”
Section: Introductionmentioning
confidence: 99%
“…Reference or standard oximes are usually specific to individual OP compounds and are not broad-spectrum [ 3 , 4 , 5 , 6 , 7 ]. In addition to the lack of universal access, another problem with reference oximes is their pharmacological properties, which are defined by their rapid dissociation in the body into ionized forms [ 8 , 9 , 10 ]. Hydrophilic oximes with a charged nitrogen atom hardly pass through the blood–brain barrier (BBB) to central synapses.…”
Section: Introductionmentioning
confidence: 99%
“…Reference or standard oximes are usually specific to individual OP compounds and are not broad-spectrum [3][4][5][6][7]. In addition to the lack of 2 universal access, another problem with reference oximes is their pharmacological properties, which are defined by their rapid dissociation in the body into ionized form [8]. Hydrophilic oximes with a charged nitrogen atom hardly pass through the blood-brain barrier (BBB) to central synapses.…”
Section: Introductionmentioning
confidence: 99%
“…Irwin Wilson found that an oxime restored acetylcholinesterase activity by chemically removing the inhibitor from serine at the active site (Wilson & Ginsburg, 1955). Oximes are now a standard antidote used for treatment of poisoning by nerve agents and organophosphorus pesticides (Thiermann & Worek, 2022).…”
Section: Introductionmentioning
confidence: 99%